Veld condition indexing : relevance to wildlife management? - Cumming, Shannon (Department of Biological Sciences, 2017)
Rangelands (veld) form part of an important renewable resource. · Measurement and monitoring of veld condition is an important management tool. Management methods need to be centred on the objectives of the livestock farm or game reserve being managed. Veld condition assessments and their use in managing stocking rates are dependent on the range succession model, which sets out the concept of directional successional changes in species composition. Although this rangeland succession model has been widely criticised it is still extensively used for veld management in South Africa. Many variations of veld condition assessment methods have been developed to be used as a tool for making informed management decisions. The Ecological Index Method was the focus of this study. The general expectation of the relationship between veld condition and animal biomass is that the greatest biomass should be in areas of high veld condition. Soil condition and habitat structure were also explored in terms of their relationship with the veld condition index. Animal biomass was found to decrease slightly with increasing veld condition index scores. There was little to no relationship between VCI and species diversity and evenness. Herbivore species displayed a range of habitat preferences in terms of VCI scores, grass height and tree basal area. This indicated that habitat choices may not have only been influenced by forage quality but also by ability to graze different grass heights, based on jaw morphology, and the risk of predation. The relationship between VCI and veld condition variables was found to be triangular due to the method of calculation causing the VCI to fold back on itself. This complicates interpretation of results. The results of this study suggest that either the interpretation of the index needs to be reconsidered for a game reserve context or a new method needs to be developed.